Luminous creatures : the history and science of light production in living organisms - Anctil, Michel, 1945- (McGill-Queen's University Press, 2018)
"Charles Darwin was perplexed by the chaotic diversity of luminous organisms, which he found difficult to reconcile with his evolutionary theory. For other reasons bewilderment confronted many observers watching living lights throughout the ages. It fell on naturalists and scientists to try and make sense of the dazzling luminous displays by fireflies and other organisms. In Luminous Creatures, Michel Anctil shows how the mythical perceptions of bioluminescence gradually gave way to a scientific understanding of its mechanisms, functions and evolution, and to the recognition of its usefulness for biomedical and other applied fields. Naturalists since the Antiquity worked hard at dispelling fanciful ideas about the meaning of living lights by giving as reliable accounts of what they saw as was in their power. But it took the circumnavigations and oceanographic expeditions of the eighteenth and nineteenth centuries, and the rise of the modern scientific method, for biologists to realize how widespread bioluminescence is on the planet and how diverse are its expressions in light organs and ecological imprints. By the end of the nineteenth century an understanding of the chemical nature and physiological control of the phenomenon was at hand. Technological developments led to the recent explosion of knowledge on the ecology, evolution and molecular biology of bioluminescence. Luminous Creatures tracks these historical events and illuminates the lives and trail-blazing accomplishments of the scientists involved. It offers a unique window in the awe-inspiring, phantasmagorical world of light-producing organisms, viewed from the perspectives of the casual observer and science-maker alike."--